De Gele Rijder : tentoonstellingen 1994. - Assmann, Gijs; Kuitenbrouwer, Mirjam; Meuve, L.; Smeets, Tanja; van de Pals, Anne; van Hout, Seet; van der Weide, Albert; De Gele Rijder, Arnhem (Arnhem : De Gele Rijder, 1995)
Kamphuis, Ivo ; de Pals, Anne van ; Sigurdardottir, Ragna ; Staartjes, Astrid ; Mandersloot, Frank ; Villevoye, Roy ; Duinkerken, René ; Duinkerken, Jan ; Merx, Jan ; Sohier, Roland ; van der Jagt, Ante ; Assmann, Gijs ; Scholten, Michel ; Meliani, Laila ; van Riessen, Wouter ; Manders, Mark ; van den Bosch, Mattijs ; van Dijk, Cor ; van der Putten, Hendri ; Smeets, Tanja ; Cuppens, Noëlle
Nederlands
boek